Effects of cetylpyridinium chloride treatment of roast beef on Listeria monocytogenes populations and quality attributes - Singh, M.; Thippareddi, H.; Herald, T.J.; Phebus, Randall K.; Marsden, James L.; Nutsch, Abbey L. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
The effectiveness of cetylpyridinium chloride (CPC) for reducing microbial populations, in particular Listeria monocytogenes, on ready-to-eat roast beef was evaluated. Roast beef slices inoculated with L. monocytogenes were dipped in a solution of 1% CPC for 1 minute. Samples were then vacuum packaged and stored at refrigeration temperature. The effects of CPC treatment on microbial populations, as well as on color and texture of the roast beef samples, was evaluated over a 42-day period. Immediately after CPC treatment, L. monocytogenes populations were reduced by 99 to 99.99%, with the treatment being somewhat more effective on exterior than on sliced/cut surfaces. Throughout 42 days of refrigerated storage, populations of L. monocytogenes, total bacteria, and lactic acid bacteria remained lower on CPC-treated samples than on non-treated samples. Treatment with CPC did not significantly affect the color or texture of roast beef. Treatment with CPC, especially when applied to products before slicing, may serve as an effective antimicrobial intervention for ready-to-eat meat products.
Keywords: Beef; Cetylpyridinium chloride; Listeria monocytogenes; Roast beef